The Evolution of Powell Basin (Antarctica) - Alberto Santamaría Barragán; Manuel Catalán; Yasmina M. Martos (Remote Sensing)
Powell Basin is an ocean basin formed as a result of the Scotia Sea evolution. The existing tectonic models propose a variety of starting and ending ages for the spreading of the basin based on seafloor magnetic anomalies. Here, we use recent magnetic field data obtained from eight magnetic profiles in Powell Basin to provide insights into the oceanic spreading evolution. The differences found between the number of anomalies on both sides of the axis and the asymmetry in the spreading rates suggest different opening models for different parts of the basin. We propose a spreading model starting in the late Eocene (38.08 Ma) and ending in the early Miocene (21.8 Ma) for the northern part of Powell Basin. For the southern part, the opening started in the late Eocene (38.08 Ma) and ended in the middle Paleogene (25.2 Ma). The magnetic data have been combined with gravity and sediment thickness data to better constrain the age models. The gravity and sediment thickness information allow us to more accurately locate the position of the extinct spreading axis. Geothermal heat flow measurements are used to understand the relationship between the low amplitudes of the magnetic anomalies and the heat beneath them. Our proposed oceanic spreading models suggest that the initial incursions of the Pacific mantle outflow into the Powell Basin occurred in the Oligocene, and the initial incursions of oceanic currents from the Weddell Sea occurred in the Eocene.